دور الإدارة الإلكترونية في تحقيق الاعتماد المؤسسي والبرامجي في مؤسسات التعليم العالي الليبية: دراسة ميدانية في كلية صرمان للعلوم والتقنية - عبد الكريم ساسي النسر; فوزية علي يونس (Surman Journal of Science and Technology, 2025)
This study aimed to identify the role of e-administration in achieving institutional and program accreditation in Libyan higher education institutions. The field study was conducted at the Surman College of Science and Technology. To achieve the study's objectives, the descriptive-analytical method was used, along with a questionnaire to collect, analyze, and interpret data and information using SPSS software, which includes a suite of statistical tests. The study concluded that there is a strong and statistically significant positive relationship and impact of the electronic system used on institutional and program performance. This dimension is the most influential of the four dimensions, followed by the dimension of senior management awareness and culture, which ranks second in terms of impact. The study offers several recommendations, most notably identifying the requirements for infrastructure quality and the challenges that limit the use of these technologies in terms of human and material resources and the development of electronic software. Additionally, it recommends establishing a database within the college and linking all its offices and departments to it to facilitate rapid information exchange and access. The college administration should also focus on the optimal and broader use of digital technology in all administrative, educational, and library aspects to achieve institutional and program accreditation. This includes prioritizing the effective use of information and communication technology within the college, implementing e-administration to enable faculty and students to quickly access books and research papers, and utilizing an electronic library card system.